2023
DOI: 10.3390/polym15102344
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Application Progress of Imprinted Polymers

Abstract: Due to the specific recognition performance, imprinted polymers have been widely investigated and applied in the field of separation and detection. Based on the introduction of the imprinting principles, the classification of imprinted polymers (bulk imprinting, surface imprinting, and epitope imprinting) are summarized according to their structure first. Secondly, the preparation methods of imprinted polymers are summarized in detail, including traditional thermal polymerization, novel radiation polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Molecularly imprinted polymers (MIPs) are porous matter fabricated via imprinting technology, which has perfect selectivity for the templates in spatial structure and binding sites [7]. According to the location of templates distributed into the imprinted polymers, the MIPs can be classified as traditional bulk MIPs, novel surface MIPs, and epitope MIPs [8]. Bulk MIPs are the first-generation products with imprinting technology, which are prepared with template-functional monomer complex, cross-linkers, and initiators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecularly imprinted polymers (MIPs) are porous matter fabricated via imprinting technology, which has perfect selectivity for the templates in spatial structure and binding sites [7]. According to the location of templates distributed into the imprinted polymers, the MIPs can be classified as traditional bulk MIPs, novel surface MIPs, and epitope MIPs [8]. Bulk MIPs are the first-generation products with imprinting technology, which are prepared with template-functional monomer complex, cross-linkers, and initiators.…”
Section: Introductionmentioning
confidence: 99%
“…Novel irradiation polymerization was developed for the fabrication of MIPs, especially for the electron beam (EB) irradiation polymerization, which not only shortens the preparation time, but also avoids environmental pollution and initiator residue [8,9]. MIPs of sulfamethazine were prepared by EB irradiation polymerization [18], wherein the optimal irradiation dose was found to be 150 kGy, the maximum adsorption capacity of sulfamethazine was 31 mg/g, and the imprinting factor was as high as 12.91.…”
Section: Introductionmentioning
confidence: 99%
“…[73] This also showed that the synthesized MIP (2VP) was more selective The successful imprinting process of MIP significantly contributed to its selectivity towards ATZ, demonstrating remarkable recognition ability despite the minimal structural differences among the competitive compounds, thus highlighting the combined influence of shape and size complementarity alongside analyte-functional group interactions within the three-dimensional polymer network. [33]…”
Section: Selectivity Testmentioning
confidence: 99%
“…The molecular imprinting process allows for precise control over the shape, size, and distribution of binding sites within the polymer matrix, enabling tailored interactions with the template molecules [32] . Furthermore, MIPs offer excellent stability, high affinity, high selectivity, simple, and inexpensive preparation, [33] which are crucial factors for sustainable and cost‐effective environmental conservation strategies. Commonly, there are various options for MIP preparation such as traditional thermal polymerization, novel radiation polymerization, and green polymerization and the produced MIPs are useful for numerous applications including separation and detection [34] .…”
Section: Introductionmentioning
confidence: 99%
“…We provide a comprehensive summarization of coal water slurry dispersants [17]. Diverse types of CWS dispersants exist, as illustrated in Table 1.…”
Section: Classification and Characteristics Of Cws Dispersantsmentioning
confidence: 99%